COVID-19 IMPLICATION FOR BUSINESS GROWTH: - Rendy Oratmangun (Jurnal Ilmiah Hospitality, 2022)
Since the Corona Virus outbreak in 2019, there have been several threats as well as the benefits for the business community but most people felt the negative effect of this outbreak. People force to face threat on health, mental health, losing job, losing exponential growth of their business, but on the other side several health business growth exponentially as well as digital technology, they grow in immense quantity, Goddevrind V, Schumacher T, Seetharaman R, & Spillecke D, (2021) in their research about C2C e-commerce showing that there are massive adoption of digitalization which is jump 14% for the growth that would take two or three years and still growth about 8% or 9% to 2024. In this study, researchers try to understand in a deeper situation for the next normal which is the term for people to be hand in hand with this outbreak, people to live with it, as well as in the context of business. Several researches have been done to understand this situation, but what defines the difference for this research is the widest variables applied in order to grasp a broader view. Variables used such as; human innovation, commodity, labor, technology, policy and how differ generations perceive such an outbreak. Quantitative approach will be used in this study, and making sure that this research will fulfill its objective, researchers applied multivariate analysis (Manova) as a statistical tool. Innovations made by each individual for business growth affect the distribution of goods and services and do not affect the production of goods and/or services and the amount of consumption during the Covid-19 pandemic in Saumlaki. The limited number of workers during the Covid-19 pandemic affected quantity of production in Saumlaki but did not affect distribution and consumption. Policies made by the Government affect consumption of society in the business but do not affect production and distribution. Whereas during the Covid-19 pandemic, commodities, technology and generational differences did not affect business growth at all, such as production for businesses, distribution for businesses and consumption for businesses in Saumlaki.